Geospatial Modelling For Potential High Risk Tuberculosis Areas In Shah Alam, Selangor - Rasam, Abdul Rauf Abdul (2018)
Malaysia has a medium burden of tuberculosis (TB) incidence based on World Health Organization (WHO) indicator, but the current trend of TB cases is generally increasing. The Ministry of Health (MOH), Malaysia has set up several guidelines to control the disease, however, the national TB technical report in 2015 highlighted that existing detection methods of TB on the site still need to be improved to strenghten the current TB control programme. A geospatial model is proposed in this study to identify potential high-risk areas of TB and targeted risk population especially for missing cases and undiagnosed people.